The Portrayals of the Other in Yemeni Postcolonial Fiction: A Critical Study on Ahmed Zein’s Steamer Point - Ba-fadhel, Nawal; Manqoush, Riyad (International Journal of Language and Literary Studies, 2024)
This research paper investigates the portrayals of the other in Ahmed Zein’s Steamer Point (2015), with a special focus on the European colonizer. In addition to that, it examines the coexistence between the natives and Europeans as reflected in the story. The postcolonial theory has been used as a methodology to frame the discussions and analysis of the novel in this study. The paper has been constructed in five sections: Introduction, background of the study, theoretical framework, discussions and analysis, and finally the conclusion. The study ended up with the conclusion that The relationship between the self and the other is one of the complicated issues in the postcolonial era. Each one of self and other seeks to abolish the boundaries between them. The other seeks to abolish the components of the self, which make the self feels the loss of his privacy and rights in his relationship with the other. Steamer Point dealt with the issue of colonization and the relationship between the colonizer and the colonized people. While the story seems to glorify the colonizers, it also showed their real face in the negative way they looked at the natives, as well as how badly they treated them. That hegemony and biasness against the local people led at the end of the story to independence.